Description of the viral community in fecal content of common carp (Cyprinus carpio) living in a naturally preserved wetland on Mexican plateau - Torres-Meza, Oscar Abel; Godoy-Lozano, Elizabeth Ernestina; Rico-Chávez, Oscar; Loza-Rubio, Elizabeth; García-Espinosa, Gary (Frontiers in Aquaculture, 2024)
The common carp (Cyprinus carpio) is a species that has been used worldwide as a source of protein for humans because of its adaptive capacity to the environment; however, it is also an invasive species. In Mexico, it was introduced to provide an easily accessible source of protein to people in rural areas until its extensive nationwide distribution. The community of viruses in these fish is not completely known. Massive sequencing, i.e., whole metagenome shotgun (WMS) sequencing, and bioinformatic analysis were used to describe the viral community of common carp (Cyprinus carpio) living in a natural preserved wetland. Through sequencer Illumina NextSeq 500/550 we got 484,953,684 sequences from ten samples of fecal content of carp (5 samples to DNA and 5 samples to RNA). The virome comprised 30 viral families (13 DNA families and 17 RNA families), among which viruses related to vertebrates stood out, for example Orthoherpesviridae, Parvoviridae, Astroviridae, Poxviridae, Hantaviridae and Picornaviridae. On the other hand, the most abundant viral taxa corresponded to bacteriophages, most of which are of polyphyletic origin. The results of this work contribute to the knowledge of the different viral taxa found in the common carp in the wild and indicate that these viral taxa may play a role in health and productivity of fish farms.